Samlevnad som ideologi i migrationslagstiftningen (Sociologisk Forskning, 2017)
Cohabitation as ideology in migration lawIn this study we study how homosexuality has legally gone from exclusion to inclusion in migration law and what ideological understandings that underpin this inclusion. The data corpus of the study consisted of the preparatory work concerning same-sex sexuality, cohabitation and migration. Data was coded for patterns concerning the public administrative understandings of same-sex sexuality as described in the preparatory works. The coding was theoretically driven by critical and Marxist approaches to ideology. Conducting a thematic analysis, four themes were identified in the data. The overall finding is that the preparatory works give precedence to sexuality in terms of disposition (läggning) when it is linked to identity and intensions to engage in a long-term relationship. This means that alternative sexual identities and practices not compatible with the ”heterosexual matrix” have been excluded from the ideological lens. The ideological focus in the preparatory works could be seen as a reflection of the capitalist system, where some social categories are viewed as desirable to include in a capitalist society.
Keywords: migration law; asylum; gay and lesbian; queer; Marxism